Strategy and Quality of Translation of Nusantara Culinary Terms from Indonesian into Arabic - Muhamad Saiful Mukminin; Hidayat Muhammad Sidiq; Fakhimatul Usroh; Nilna Dati Layyina; Yunia Makin Aninda Fiqrotin Nisa'; Muhammad Yunus Anis (CMES (Center of Middle Eastern Studies), 2022)
The development of the Nusantara culinary industry throughout the world shows that Nusantara culinary products are a prospective business opportunity. The presence of Nusantara culinary as a business opportunity in the world requires an understanding of culinary terms in promoting Nusantara culinary terms. One of the areas that makes Nusantara culinary a culinary business opportunity is the Middle East region. The massive use of Arabic in the Middle East requires the equivalent of Nusantara culinary terms in Arabic as well. This requires a translation process between Indonesian and Arabic. This study describes the strategy of translating Indonesian-Arabic Nusantara culinary terms. Data were collected from various corpus of data in the form of 3 Indonesian-Arabic dictionaries and 1 internet page source. The findings of the translation strategy are in the form of 204 data on the translation of three types of Indonesian-Arabic Nusantara culinary terms. The findings of the syntactic strategy there are 4 types of syntactic translation strategies applied, namely literal translation of 17 (8.5%) data, 17 (8.5%), borrowing of 17 (8.5%), unit shifting 160 (80%), and changing the phrase structure 6 (3%) data. There is only one type of semantic strategy application, namely hyponyms as much as 82 (40%) data. The implementation of the pragmatic strategy found two strategies, namely cultural filtering of 11 (5.4%) data and changing of information as much as 8 (3.9%) data. The results of the assessment of the quality of the translation of the Nusantara culinary term obtained a level of accuracy that is less accurate, acceptability is less acceptable, and legibility is legible.